Diseases with oral manifestations among adult asthmatics in Finland: a population-based matched cohort study. Issue 12 (31st December 2021) - Lemmetyinen, Riikka; Karjalainen, Jussi; But, Anna; Renkonen, Risto; Pekkanen, Juha; Haukka, Jari; Toppila-Salmi, Sanna
Abstract : Objectives: Many comorbidities are associated with adult asthma and may exacerbate the asthma burden of disease. This study aims to investigate the risk for major oral diseases or oral-manifesting diseases in asthmatic compared with non-asthmatic adults. Design: We conducted a population-based matched cohort study with a 13.8-year follow-up. Setting: A baseline questionnaire was completed by participants in 1997 and follow-up data were extracted from the national hospital discharge registry of the National Institute for Health and Welfare in Finland from 1997 to 2014. Participants: A total of 1394 adults with asthma were matched with 2398 adults without asthma based on sex, age and area of residence. Asthmatic adults were identified from the Drug Reimbursement Register of the Finnish Social Insurance Institution based on a special drug reimbursement right resulting from asthma. Participants without asthma were identified from the Population Register. Main outcomes and measures: Oral health-related primary diagnoses were retrieved using codes from the International Classification of Diseases, 10th edition and divided into groups of diseases. Cox's proportional hazards models stratified by matching unit and models matched and adjusted for pack-years, education level and body mass index (when possible) were used to evaluate the matched and further adjusted HRs for diseases comparing asthmatic and non-asthmatic cohorts. Results: Adult asthma was associated with a higher risk for any oral-manifesting disease (adjusted HR 1.41, 95% CI 1.11 to 1.80), herpes zoster (adjusted HR 6.18, 95% CI 1.21 to 31.6), benign tumours of the oral cavity and pharynx (matched HR 1.94, 95% CI 1.05 to 3.56) and dermatological diseases (pemphigus, pemphigoid, dermatitis herpetiformis, psoriasis and lichen planus, HR 1.67, 95% CI 1.01 to 2.78). Conclusions: In this study, adult asthmatics experienced a higher risk for a major oral disease or oral-manifesting disease.